2022
DOI: 10.1186/s12967-022-03292-z
|View full text |Cite
|
Sign up to set email alerts
|

In vivo detection of dysregulated choline metabolism in paclitaxel-resistant ovarian cancers with proton magnetic resonance spectroscopy

Abstract: Background Chemoresistance gradually develops during treatment of epithelial ovarian cancer (EOC). Metabolic alterations, especially in vivo easily detectable metabolites in paclitaxel (PTX)-resistant EOC remain unclear. Methods Xenograft models of the PTX-sensitive and PTX-resistant EOCs were built. Using a combination of in vivo proton-magnetic resonance spectroscopy (1H-MRS), metabolomics and proteomics, we investigated the in vivo metabolites a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 52 publications
(51 reference statements)
1
7
0
Order By: Relevance
“…LGALS2 reportedly inhibits the development of CRC and lymph node metastasis of gastric cancer [50,51]. GDE1 expression is significantly reduced in drugresistant ovarian cancer samples [52]. Consistent with these findings, our results suggested that high expression of LGALS2 and GDE1 in CRC patients implies a good prognosis.…”
Section: Elevated Expression Ofsupporting
confidence: 87%
“…LGALS2 reportedly inhibits the development of CRC and lymph node metastasis of gastric cancer [50,51]. GDE1 expression is significantly reduced in drugresistant ovarian cancer samples [52]. Consistent with these findings, our results suggested that high expression of LGALS2 and GDE1 in CRC patients implies a good prognosis.…”
Section: Elevated Expression Ofsupporting
confidence: 87%
“…As far as the genes in riskscore model are concerned, we have found that GDE1, GSR, TAMM41 and TIGD6 are favorable prognostic genes, while HSPB1, AOC2, and TBX19 are risk genes. Glycerophosphodiester phosphodiesterase 1 (GDE1) has been identified as a key enzyme associated with paclitaxel resistance in ovarian cancer 16 . Decreased expressions of GDE1 choline metabolism could elevate glycerophosphocholine levels in the paclitaxel‐resistant epithelial ovarian cancer 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Not only does metabolic adaptation of tumors take place throughout the course of OC, but it also happens during the course of therapy, which results in drug resistance (134)(135)(136)(137). Metabolic reprogramming of the TIME in ovarian cancer leads to chemoresistance.…”
Section: Immunotherapeutic Strategies Targeting Time Metabolic Reprog...mentioning
confidence: 99%
“…Moreover, paclitaxel resistance in ovarian cancer is associated with choline metabolism reprogramming. The expression of glycerophosphocholine phosphodiesterase 1 and glycerophosphodiester phosphodiesterase 1 in EOC was discovered to be elevated using proton magnetic resonance spectroscopy, and total choline was found to be elevated (136). Owing to the cunning metabolic adaptations of OC, monotherapy is frequently ineffective.…”
Section: Immunotherapeutic Strategies Targeting Time Metabolic Reprog...mentioning
confidence: 99%